The application of CBL and mind mapping combined with Mini-CEX teaching mode in the cultivation of clinical competence of ultrasound residents - Rong Liu; Lei Li; Ying Zhou; Lu Xiong (PLoS ONE, 2025)
Objective This study aims to evaluate the efficacy of the Mini Clinical Evaluation Exercise (Mini-CEX) in conjunction with Case-Based Learning (CBL) and mind mapping methodologies in fostering the clinical competencies of ultrasound residents. Methods A cohort of forty-two general practitioners who underwent standardized training at the Department of Ultrasound Medicine at Tianyou Hospital, affiliated with Wuhan University of Science and Technology, from December 1, 2022 to December 1, 2024, were selected for this research. These practitioners were randomly assigned to either an experimental group or a control group using a random number table. The experimental group engaged in training utilizing the Mini-CEX combined with CBL and mind mapping approach, whereas the control group adhered to a traditional training regimen. Subsequently, comparative analyses were conducted on theoretical and practical test scores as well as clinical teaching satisfaction ratings between the two groups. Additionally, variations in Mini-CEX evaluation scores for the experimental group were assessed at admission, after two weeks, and after four weeks of training. Results The training approach that integrated Mini-CEX with CBL and mind mapping demonstrated significantly superior outcomes compared to the traditional training method regarding theoretical and practical performance, as well as teaching satisfaction, with statistically significant differences noted (p < 0.05). A comparison of Mini-CEX scores among 21 general practitioners at two and four weeks post-training versus admission yielded statistically significant results (p < 0.05). Conclusion The amalgamation of Mini-CEX with CBL and mind mapping methodologies markedly enhances the instructional effectiveness of standardized resident training.